Atonement The Person and Work of Christ - Torrance, Thomas F. (Milton Keynes ; Colorado Springs : Paternoster ; Downers Grove, Ill. IVP Academic, 2009)
This companion volume to T.F. Torrance's Incarnation: The Person and Life of Christ presents the material on the work of Christ, centered in the atonement, given originally in his lectures delivered to his students in Christian Dogmatics on Christology
Keywords: Jesus Christ -- Resurrection. Jesus Christ -- Person and offices. Atonement